An OPTIMALIZATION OF HEALTH CARE PRACTICIONERS ROLE IN EARLY DETECTION OF STUNTING IN STUNTING LOCUS VILLAGE: Optimalisasi Peran Praktisi Tenaga Kesehatan dalam Deteksi Dini Stunting di Desa Lokus Stunting - Esme Anggeriyane (Borneo Community Development, 2022)
The growth and development of a child needs to be considered by parents starting with the first 1000 days of birth (in Bahasa is Hari Pertama Kelahiran/ HPK). But in reality, in Barito Kuala it was found that there are still many infants and toddlers who need to be considered for their growth and development, such as anthropometric examinations which indicate a child is stunted. The purpose of this activity was for early detection of stunting in children in Tabukan Raya Village, which is a Stunting Locus Village. The method of implementation was by checking the body height or length associated with the gender and age of the target. Conclusions were made in 4 categories, namely severely stunted, stunted, normal and tall, referring to the WHO growth curve. The results of the screening showed that in Tabukan Raya Village there were still children with indications of being severely stunted and stunted, each with a total of 4 people (8.16%). The activity was carried out in an orderly and smooth manner and parents received education about stunting to optimize children's growth and development.